IMPLEMENTASI PENDEKATAN SAINTIFIK PADA MATA PELAJARAN PENDIDIKAN AGAMA DAN BUDI PEKERTI ERA PANDEMI COVID-19 DI SMA NEGERI 8 KOTA MALANG - Farha Qonita; Anwar Sa’dullah; Adi Sudrajat (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
Since the government's policy during the Covid-19 pandemic that started conventional learning to learning (online), schools have made various efforts so that learning runs optimally. One of them is online and offline learning with an odd-even system. The iimplementation of learning still carried out in acordance the 2013 curriculum which uses a scientific approach which contains five aspects of the learning process, namely observing, asking questions, gatering information, asociating and comunicating. Some of the obstacles that occur when implementing a scientific approach during a pandemic. Both come from educators, students, learning facilities and media. Base on the resutls of research in the fieeld, it was found that student tend to be active in the aspect of asking questions,and gathering information during a pandemic is dominated by online sources such as those from websites and blogs. Kata Kunci: saintifik, PAI, Pembelajaran Daring